Use of an Approach for Preventing Test Debt in a Brazilian Fintech: An Experience Report - Silva, Levi Almeida; Santos, Ismayle Sousa; Andrade, Rossana Maria de Castro (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
The demand for software innovation has challenged organizations to meet deadlines and quality standards. Technical Debt (TD) refers to aspects of software development that are deferred to achieve immediate benefits but result in negative consequences for the product’s long-term quality. In the software development cycle, the Testing phase also accumulates Technical Debt, known as Test Debt, compromising this stage. Aiming to support the management of such debts, this paper aims to present an experience report on the application of strategies to prevent Test Debt in a Brazilian fintech. This work describes how the approach was implemented, the results obtained, and the lessons learned from the experience.